Aktivitas Antibakteri Kombinasi Vitamin C dan Amoksisilin sebagai Bahan Alternatif Intrakanal Medikamen terhadap Enterococcus faecalis secara In Vitro - Julia Eka Putri Ayuningtyas; Pudji Astuti; Dwi Warna Aju Fatmawati (UPT Percetakan dan Penerbitan Universitas Jember, 2021)
Bacteria that are often found in cases of pulp necrosis and root canal treatment are Enterococcus faecalis. Elimination of microorganisms in the root canal can use intracanal medicament. The intracanal medicament can be used from antibiotics such as amoxicillin. The antibacterial power of amoxicillin can be increased by combination with vitamin C to prevent resistance. This research aimed to determine the zone of inhibition of vitamin C and amoxicillin against Enterococcus faecalis. The method used in this study is well diffusion method. Inhibition is shown through the clear zone around the wellbore at 24 hours, 48 ​​hours, 72 hours after incubation. The number of research samples is 16 consisted of 4 groups consisting of amoxicillin, vitamin C, a combination of vitamin C and amoxicillin, and 3 MIX MP. The data were tested by non-parametric statistical analysis Kruskal Wallis and Mann Whitney. The result showed that vitamin C and amoxicillin's antibacterial activity as alternative material intracanal medicament is equivalent to antibacterial 3 MIX MP.